The Hippo Signaling Pathway and Cancer - Oren, Moshe; Aylon, Yael.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
The Hippo signaling pathway is rapidly gaining recognition as an important player in organ size control and tumorgenesis. This volume presents virtually all aspects of tumor biology because members of the Hippo Pathway have been associated with numerous well-established cell signaling pathways, just to name a few; Rho, Wnt, TGFbeta and p53. Hippo signaling is not solely involved in regulating (3z(Bclassic(3y (Btumor characteristics such as cell proliferation, survival and growth, but is also diversely involved in cell-autonomous and non-cell-autonomous differentiation, migration and organ size control. With the multitude of signaling events mediated by the Hippo pathway and the vastly different functions that it plays, it is evident that these tumor suppressors are unique governors of cellular homeostasis. This timely volume gathers wide-ranging and burgeoning information on the Hippo pathway and its role in cancer into an accessible format of a single book.With the multitude of signaling events mediated by the Hippo pathway and the vastly different functions that it plays, it is evident that these tumor suppressors are unique governors of cellular homeostasis. This timely volume gathers wide-ranging and burgeoning information on the Hippo pathway and its role in cancer into an accessible format of a single book.s
Introduction -- Merlin and Angiomotin in Hippo-Yap signaling -- MST1/2 and other upstream signaling that affect Hippo pathway function -- YAP1 uses its modular protein domains and conserved sequence motifs to orchestrate diverse repertoires of signaling -- Regulation of YAP and TAZ transcription co-activators -- Regulation of YAP and TAZ by epithelial plasticity -- Hippo pathway and apoptosis -- YAP and p73: a matter of mutual specificity in tumour suppression -- The c-Abl/YAP/p73 apoptotic module and the Hippo pathway -- Hippo in cell cycle and mitosis -- Hippo and mouse models for cancer -- Roles of Hippo signaling during mouse embryogenesis -- Hippo Signaling and stem cells -- Hippo signaling and organ size control -- Hippo signaling in heart development -- Cell competition and the Hippo pathway -- Non-canonical roles from the Hippo pathway -- Index.
Keywords: Medicine; Oncology; Microbiology; Cytology; Biomedicine; Cancer Research; Cell Biology; Medical Microbiology; Biomedicine general